Prospects and challenges of introducing software in banking sector: a case study on Shahjalal Islami Bank Limited - Azad, Kornica (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.